DETERMINATION OF CHANGES IN THE PATHOGENICITY FACTORS ACTIVITY OF THE ORAL CAVITY MICROFLORA IN PATIENTS WITH SECONDARY ADENTIA DEPENDING ON THE TAME OF DAY - Yuliia Slynko; Maryna Mishyna; Iryna Sokolova; Yuliya Mozgova; Iryna Marchenko; Olena Dubovyk; Olena Gopta (Romanian Society of Oral Rehabilitation, 2022)
Investigation of biological properties in microorganisms remain relevant to the current stage of dentistry development. The aim of this work was to study the adhesive and enzymatic activity of oral microbioma representatives with determination of ability to form biofilms at different times of day Materials and methods. The total of 35 patients with partial secondary adentia were involved in the study. Studies in 35 patients who were in the stages of examination and preparation for the dental implantation surgery on partial secondary adentia (included small single or bilateral defects). Ability to form biofilms and the enzymatic activity was studied in Staphylococcus aureus, Streptococcus mutans, Candida Albicans and Hafnia Alvei at 9, 12, 15 and 18 hours. Results. It has been established that the high activity of enzymes and the ability to form biofilm occurs during times when medical manipulations are the most frequently carried out - at 1200 and 1500. The peaks of reduced pathogenicity factors production were recorded at 9.00 and about 18.00. Conclusions. The obtained results can be used for optimal planning of rehabilitation manipulations (dental implantation operations) in the oral cavity in individuals with secondary adentia.